(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This research measuring the radioactive gas radon in samples of drinking water in the schools of Abu- Gharaq in Babylon Governorate Was chosen as the water from 14 schools by using the electronic radon detector RADH2O, where the highest value (0.688) Bq.L-1 and the lowest value (0.072) Bq.L-1 and effective dose for, human exposure to radon rate from (0.31536) mSv.y-1 to (3.01344 (mSv.y-1.This subject Has been chosen for the importance of water in human life and the lack of previous studies in the study area.